Pengaruh Stress Kerja, Employee Relation Terhadap Motivasi yang Berdampak pada Organizational Citizenship Behaviour - Wini Agustin; Eka Bertuah (MES Management Journal, 2024)
This study aims to examine the effect of job stress and the relationship between employees on employee motivation, which in turn has an impact on organizational citizenship behavior (OCB). This study uses the survey method to collect data through a questionnaire given to 132 respondents who work for the company that is the object of the research. Furthermore, data analysis was carried out using the PLS-SEM technique. The results of the study found that variable employee relations have a positive effect on motivation. Then employee relations have a positive effect on organizational citizenship behavior. Then the motivation variable has a positive effect on organizational citizenship behavior. Furthermore, the variable job stress has a negative effect on motivation. Furthermore, the job stress variable has no effect on organizational citizenship behavior. Then, using motivation as a mediating variable, it was found that there is a positive influence of employee relations on organizational citizenship behavior with motivation as mediation. Then it was found that there is a positive effect of job stress on organizational citizenship behavior, with motivation as the mediator.